Periumbilical fat graft: a new resource to replace large volume in the orbit. (October 2014) - Medel, Ramon; Vasquez, LuzMaria
Abstract Goal: To describe the technique we use to obtain a fat graft from the periumbilical area to replace volume in our patients requiring total or partial orbital volume restoration or replacement. Materials and methods: Under local anaesthesia a one-piece fat auto-graft is obtained from one of the quadrants of the periumbilical zone through a 10- to 15-mm incision at the umbilicus edge. Results: Excised adipose tissue contains connective tracts, with medium and small vascular vessels with discrete thickened wall and preserved endothelium, with more blood cells, and less dead cells. Conclusions: Fat grafts are the ideal fillers for patients requiring orbital volume replacement. The periumbilical fat graft technique we describe is simple, safe and fast, the learning slope shallow and the results gratifying in both the replaced volume, and the donor area with an invisible scar. The amount of fat that can be obtained with this technique through a minimal incision can be large enough.